Ionising Radiation and Mankind - Gopinath, D. V.; Ramamoorthy, N. (Cambridge Scholars Publishing, 2020)
This book provides a comprehensive account of the developments and current status in several fields of the application of radioactivity and ionising radiation. It covers such topics as radiation-based techniques, radiation's applications in medicine, food and agriculture, its impact on industry, and its associated materials. The book will be of interest to a wide variety of readers including professionals in radiation medicine, industrial processes, food preservation, and agriculture.